HRM and Its Effect on Employee, Organizational, and Financial Outcomes in Organizations - Talapbayeva, G.E.; Yerniyazova, Z.N.; Kultanova, N.B.; Alibekova, A.B. (BUKETOV BUSINESS REVIEW, 2024)
Object: To study the impact of Human Resource Management (HRM) on employee outcomes, organizational, and financial performance. Methods: Both quantitative and qualitative data analysis methods were used. The sample included 500 employees from 100 organizations from various sectors such as manufacturing, healthcare, services and education. Data were collected through surveys and semi-structured interviews with managers and employees. Statistical methods, including regression and correlation analysis were applied using SPSS software. Results: The implementation of HRM practices improved labor productivity by 15 %, job satisfaction by 20 %, and reduced employee turnover by 10 %. There was strong correlation between HRM practices and job satisfaction (correlation coefficient of 0.70) and a negative correlation with employee turnover (-0.50). Company profits increased by 15 %, and personnel costs decreased by 10 %. Conclusions: Effective HRM practices such as employee recognition, motivation programs and continuous development contribute to increased productivity and strengthened organizational culture, leading to improved financial performance and lower turnover.